O trabalho do tutor da EaD: aproximações e distanciamentos do trabalho do docente da educação presencial - Santos, Alexandra da Silva (2020)
This present research has as theme the worker in distance education. In particular, in this study, we will treat the work developed by e-learning tutor, which acts primarily in Virtual Learning Environment (VLE), of undergraduate courses offered, at distance, in public and private educational institutions in the State of Rio de Janeiro. In this sense, we propose, as a study problem, to investigate which are the approaches and detachments of the e-learning tutor's work, which has a primary role in VLE, with the work of the traditional classroom teacher. One of the objectives is to present subsidies that contribute to expanding the understanding about the work performed by the elearning tutor and also their professional valorization. As methodological procedures for the development of this research, a questionnaire was applied followed by an interview with tutors who developed their work in the VLE of undergraduate courses offered at a distance by public and private institutions in the State of Rio de Janeiro. The collected data were analyzed in the light of references of Ricardo Antunes (1999, 2005, 2009 and 2018) and Daniel Mill (2000, 2002, 2006, 2013, 2018). The results indicated that: A) The tutor, in particular those who work directly and primarily in VLE, do not have a definition of their roles in e-learning. Despite the recognized relevant role in the student's learning process, they have not guaranteed their rights as worker, being subjugated to a job that offers low remuneration, with excessive assignments, lack of autonomy, inadequate work infrastructure, high number of students per class and temporary employment contract, characterizing the precariousness of the teaching work. B) The inquired tutors, despite not being recognized as teachers, take on this professional identity with a lot of responsibility, integrating, in their daily schedule, pedagogical activities of learning mediation, characteristics of teaching activities, letting the denomination of animator and stimulator to the documents that define (or do not define) their work. C) There is a considerable similarity between the work that is performed by the tutor and the one that is performed by the traditional classroom teacher.